Therapeutic potentials of Nigella sativa preparations and its constituents in the management of diabetes and its complications in experimental animals and patients with diabetes mellitus: A systematic review. (May 2020) - Mahmoodi, Mohammad Reza; Mohammadizadeh, Mehdi
Highlights: The N . sativa seeds and its preparations have a key role in herbal medicine as an adjuvant remedy for the treatment and management of patients with DM and its complications. The findings of the present study provide various therapeutic strategies to clarify the magnitude of N . sativa preparations on the management of DM and its complications. The mechanism of the beneficial effects N . sativa preparations for treatment and management of patients with DM and its complications are multifactorial and target simultaneously several tissues and systems. The beneficial effects of N . sativa preparations depend on dosage forms, prescribed active ingredients, and duration of the intervention. The best dosage to improve glycemic indices and lipid and lipoprotein profiles is 2 g daily powdered N . sativa for at least 12 weeks. Abstract: Objective: The purpose of this up-to-date comprehensive systematic review was to evaluate and summarize all research studies in the field in order to clarify the magnitude of Nigella sativa ( N . sativa ) effects on the management of Diabetes mellitus (DM) and its complications. Methods: A systematic review was conducted in a Cochrane style and in accordance PRISMA checklist using the published studies in PubMed/MEDLINE, SCOPUS, and EMBASE databases that were searched up to January 2019. Abstracts that met PICO criteria for qualitative studies underwent dual review for data extraction to evaluate study quality and details. Results: Dietary supplementation with N . sativa preparations can improve various secondary complications of diabetic patients. N . sativa preparations possess antidiabetic, hypoglycemic, anti-hyperlipidemic, antihypertensive, and anti-obesity effects. Beneficial effects of N . sativa preparations include the restoration of the antioxidant defense systems, the increase in the activity of antioxidant enzymes, the decrease of inflammatory biomarkers, the suppression of the production pro-inflammatory mediators, improvement of endothelial dysfunction, and hepatic, kidney, heart and immune system functions. They have key roles in managing diabetes-induced inflammation and oxidative stress in diabetic patients. Conclusion: N. sativa preparations have key roles in herbal medicine as an adjuvant in the treatment and management of patients with DM and its complications. Moreover, the beneficial effects of N. sativa preparations were differently based on dosage forms, active ingredients, and duration of intervention. The best dosage to improve glycemic indices and lipid and lipoprotein profiles is 2 g daily powdered N. sativa for at least 12 weeks.